A large randomised controlled intervention trial to prevent gastric cancer by eradication of Helicobacter pylori in Linqu County, China: baseline results and factors affecting the eradication. Issue 1 (18th May 2015) - Pan, Kai-feng; Zhang, Lian; Gerhard, Markus; Ma, Jun-ling; Liu, Wei-dong; Ulm, Kurt; Wang, Jian-xi; Zhang, Lei; Zhang, Yang; Bajbouj, Monther; Zhang, Lan-fu; Li, Ming; et al.
Abstract : Objective: To clarify the full range of benefits and adverse consequences of Helicobacter pylori eradication as a strategy for gastric cancer prevention, the community-based intervention trial was launched in Linqu County, China. Design: A total of 184 786 residents aged 25–54 years were enrolled in this trial and received 13 C-urea breath test. H. pylori positive participants were assigned into two groups, either receiving a 10-day quadruple anti- H. pylori treatment or lookalike placebos together with a single dosage of omeprazole and bismuth. Results: The prevalence of H. pylori in trial participants was 57.6%. A total of 94 101 subjects completed the treatment. The overall H. pylori eradication rate was 72.9% in the active group. Gender, body mass index, history of stomach disease, baseline delta over baseline-value of 13 C-urea breath test, missed medication doses, smoking and drinking were independent predictors of eradication failure. The missed doses and high baseline delta over baseline-value were important contributors in men and women (all Ptrend <0.001). However, a dose-response relationship between failure rate and smoking or drinking index was found in men (all Ptrend <0.001), while high body mass index (Ptrend <0.001) and history of stomach disease were significant predictors in women. The treatment failure rate increased up to 48.8% (OR 2.87, 95% CI 2.24 to 3.68) in men and 39.4% (OR 2.67, 95% CI 1.61 to 4.42) in women with multiple factors combined. Conclusions: This large community-based intervention trial to eradicate H. pylori is feasible and acceptable. The findings of this trial lead to a distinct evaluation of factors influencing eradication that should be generally considered for future eradication therapies. Trial registration number: ChiCTR-TRC-10000979 in accordance with WHO ICTRP requirements.